The Policy Analysis Positions Mutation and Its Implication to the Government Performance in Soppeng Regency - Ima Upuwala Were; Gunawan B I; Abdul Razak Munir (STIE AMKOP, 2016)
Abstract This study aims to obtain explanations about the implementation of positioning mutation in the government of Soppeng regency. The method which used in this study is descriptive type in purpose to give a fact about the implementation of positioning mutation in the goverment of Soppeng regency in case of appointment the civil servant and find out about the implication of the implementation of positioning mutation in the government of Soppeng regency. Data is analyzed qualitatively. Data collecting technique which is observation and interview library study and documentation. The results of study showed that employees are in accordance with the principles profesionalism among base on competence, work performance, and objective condition only regardless of gender, religion, rece, or groups. Mutation were held in 2016, namely in August in government shows no political implications and administrative governmance. Keywords: mutation, government.